2020
DOI: 10.1109/tmi.2019.2963446
|View full text |Cite
|
Sign up to set email alerts
|

Robust Self-Supervised Learning of Deterministic Errors in Single-Plane (Monoplanar) and Dual-Plane (Biplanar) X-Ray Fluoroscopy

Abstract: Fluoroscopic imaging that captures X-ray images at video framerates is advantageous for guiding catheter insertions by vascular surgeons and interventional radiologists. Visualizing the dynamical movements non-invasively allows complex surgical procedures to be performed with less trauma to the patient. To improve surgical precision, endovascular procedures can benefit from more accurate fluoroscopy data via calibration. This paper presents a robust self-calibration algorithm suitable for singleplane and dual-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several methods have been successfully implemented for the geometric calibration of fluoroscopy imaging systems, including global polynomial estimation [ 16 ] and maximum likelihood estimation [ 17 ]. These methods each have their relative strengths and weaknesses; the self-calibrating bundle adjustment method presented in this study also faces unique challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been successfully implemented for the geometric calibration of fluoroscopy imaging systems, including global polynomial estimation [ 16 ] and maximum likelihood estimation [ 17 ]. These methods each have their relative strengths and weaknesses; the self-calibrating bundle adjustment method presented in this study also faces unique challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also detailed the use of self-supervised methods for the accurate modeling of systematic distortion within fluoroscopy systems. This is accomplished through the integration of iterative maximum likelihood estimation and k-nearest-neighbor regression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results of rearfoot pressure comparison and Bland–Altman analysis between two methods demonstrated that the current FE model is useful under the balanced standing scenario, and subsequent validation study for the coupled model will be conducted under dynamic loading conditions. Meanwhile, it is worth noting that, with the accessibility of dual-plane fluoroscopy and high-resolution MRI, the FE model could be further validated against in vivo joint motion and soft tissue deformation data recorded by the two techniques [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%